Sinkronisasi Pendekatan Sosiologis Dengan Penemuan Hukum Islam Sui Generis Kum Empiris - Rizal Al Hamid; Arif Sugitanata; Suud Sarim Karimullah (Bertuah Jurnal Syariah dan Ekonomi Islam, 2023)
This research examines the synchronization process between the sociological approach and the empirical discovery of sui generis Islamic law. This qualitative research uses a literature study method that analyses pre-existing theories, concepts, or phenomena. The results show that the sociological approach can help understand the social and cultural factors that influence the development of Islamic law. Through this approach, it was found that Islamic values can adapt to local values according to the needs and social context of the community. Meanwhile, the discovery of empirical sui generis Islamic law is developing Islamic law by considering the social and cultural realities in which the law is applied. In this case, the research shows that the process of empirical sui generis Islamic law discovery can help produce Islamic law that is more relevant to the needs of society. Therefore, this research shows that the synchronization between the sociological approach and the discovery of sui generis Islamic law can help develop Islamic law in society's social and cultural context. This research provides practical implications for researchers and practitioners in considering the social and cultural context in developing Islamic law.